Características fisicoquímicas del aceite esencial del pericarpio de citrus reticulata l. y determinación del porcentaje relativo de sus componentes hidrocarbonados y oxigenados - Chávez León, Armando Nicolas (2016)
The objective of this research was to determine the physicochemical characteristics of oil essential extracted from the pericarp of Citrus reticulata L., obtained from food market "La Hermelinda".The oil was obtained by the method of hydrodistillation, obtaining a yield of 0.6%. The oil is crystalline in appearance, bitter taste, fresh; oily and greasy consistency and fragrance suigeneris. In addition the density obtained from this oil was 0.88086; the pH was 5.00 and the refractive index was 1.4700. This oil showed solubility in ethanol of 96 ° GL, petroleum ether and methanol. Also the percentage of hydrocarbon and oxygenates compounds were determined, which were 36.7893% and 5.3641% respectively